A complete chloroplast genome of Sedum lushanense S. S. Lai 2004 (Crassulaceae: Crassuloideae) - En-Dian Yang; Tong-Jun Liang; Zi-Yi Lei; Jie Zhang; Xiao-Xing Zhou (Mitochondrial DNA. Part B. Resources)
We determined the complete chloroplast genome sequence of Sedum lushanense S. S. Lai 2004. The genome was 148,691 bp in length, including a large single copy (LSC; 80,497 bp), a small single copy (SSC; 16,620 bp), and two inverted repeats (IR; 25,787 bp) regions. It contained 84 coding gene sequences (CDS), 34 transfer RNA (tRNA) genes, and eight ribosomal RNA (rRNA) genes. A maximum likelihood phylogenetic analysis revealed a close relationship between S. lushanense and S. lineare. Therefore, our study provided new genetic information on S. lushanense, contributing to a better understanding of its relationship with other related species and the evolutionary history of Crassulaceae.